2018
DOI: 10.1111/1346-8138.14478
|View full text |Cite
|
Sign up to set email alerts
|

Key component of inflammasome, NLRC4, was identified in the lesional epidermis of psoriatic patients

Abstract: Inflammasomes are multimolecular complexes that control the inflammatory response. The function of inflammasomes in the pathogenesis of psoriasis is still unclear. To clarify the relationship between inflammasomes and the pathophysiology of psoriasis, and in particular, to identify molecules interacting with caspase-1, a crucial component of inflammasomes, scale extracts obtained from patients with psoriasis were immunoprecipitated with anti-caspase-1 antibody and analyzed by liquid chromatography coupled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…To date, we cannot rule out a role for the NLRC4 inflammasome (or NAIP‐NLRC4) that can directly recruit caspase‐1. In a recent study, NLRC4 was found in the scale extracts of psoriasis patients; however, no inflammasome components (including NLRC4) were found in atopic dermatitis patients . Inflammasome‐independent processing of IL‐1β has been observed in a variety of settings (reviewed in).…”
Section: Discussionmentioning
confidence: 99%
“…To date, we cannot rule out a role for the NLRC4 inflammasome (or NAIP‐NLRC4) that can directly recruit caspase‐1. In a recent study, NLRC4 was found in the scale extracts of psoriasis patients; however, no inflammasome components (including NLRC4) were found in atopic dermatitis patients . Inflammasome‐independent processing of IL‐1β has been observed in a variety of settings (reviewed in).…”
Section: Discussionmentioning
confidence: 99%
“…The transcription of Naips is regulated by the transcription factor IRF‐8 . NLRC4 is implicated in the exacerbation of psoriatic lesions, and NLRP4 mutation is associated with exacerbation of asthma in smoking adults . Polymorphisms of NACHT‐LRR in NLRP12 and the promoter regions of NLRC4 and NLRP1 are associated with atopic dermatitis .…”
Section: Inflammasomementioning
confidence: 99%
“…It has also been confirmed that bacterial products can activate the NLRC4 inflammasome ( 12 ). Moreover, some studies ( 14 , 15 , 25 ) have observed that the NLRC4 inflammasome is involved in the occurrence of tumors, psoriasis and ulcerative colitis, indicating that the NLRC4 inflammasome plays an important role in the systemic inflammatory response and self-inflammatory diseases. The present study identified a causal link between NLRC4 inflammasome activation and RTEC injury.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitatively, NLRC4 staining intensity exhibited a one-fold increase in the renal tubulointerstitium of patients with DN ( 13 ). In addition, it has been revealed that the expression of NLRC4 in intestinal epithelial cells is increased and it is involved in intestinal inflammation ( 14 , 15 ). The main aim of the present study was to examine the role of the NLRC4 inflammasome in renal tubular epithelial cell (RTEC) injury in DN.…”
Section: Introductionmentioning
confidence: 99%